Analysis of leading commodities from capture fisheries resources at Bitung Oceanic Fishing Port, North Sulawesi - Kusumaningrum, Arianda; Lumingas, Lawrence L.J.; Sumilat, Deiske A.; Budiman, Johnny; Luasunaung, Alfret; Warouw, Veibe (AQUATIC SCIENCE & MANAGEMENT, 2021)
Bitung City is one of the centers of fishery production in Indonesia. Analysis of capture fisheries resources, especially at the Bitung Oceanic Fishing Port (BOFP) as a fish landing center in Bitung city, needs to be done scientifically in order to find out the need for sustainable capture fisheries. The purpose of this research is to analyze the potential of the types of superior commodities that have the opportunity to be developed. Data was collected using survey methods and in-depth interviews with fishermen and local stakeholders. Analysis of the potential of fish resources was carried out using the surplus production method. From the results of the study, it is found that there are 8 (eight) types of leading commodities in BOFP which can be developed with different potentials. They are: 1) Marlin with a sustainable potential of 159 tons, utilization rate of 44%; 2) Tongkol with sustainable potential of 10.485 tons, utilization rate is 58%; 3) Kembung with a sustainable potential of 183 tons utilization rate of 61%; 4) Big-eye tuna with sustainable potential of 111 tons utilization rate of 69%; 5) Selar with sustainable potential of 450 tons utilization rate of 85%; 6) Yellow Fin Tuna with a sustainable potential of 15.251 tons utilization rate of 86%; 7) Layang with sustainable potential of 7.152 tons utilization rate of 95%, and 8) Cakalang.Indonesian title:Â Analisis komoditas unggulan dari sumber daya perikanan tangkap di Pelabuhan Perikanan Samudera Bitung, Sulawesi Utara